NARCOTERORISM PREVENTION STRATEGY THROUGH PREDICTIVE POLICING AND THE CHALLENGES FACED BY THE POLICE IN ITS IMPLEMENTATION IN INDONESIA - M. Taufan Maulana; Eva Achjani Zulfa; Surya Nita (NOMOI Law Review, 2026)
Narcoterrorism is a crime that combines drug trafficking with acts of terrorism, where terrorist groups utilize profits from the narcotics business to fund their activities. In Indonesia, although the threat of narcotics terrorism is still relatively minimal, its potential for growth remains a serious concern given the persistently high circulation of narcotics and the rise of radicalism in society, particularly among vulnerable groups such as adolescents. Unfortunately, to date, the government and law enforcement agencies still lack an effective narcotics crime prevention strategy because they are still segmented between the war on drugs and the war on terror . Therefore, this study examines how the police implement effective prevention strategies, one of which is through predictive policing. This study uses a qualitative approach with secondary data analysis methods sourced from regulations, scientific literature, and previous research related to narcotics terrorism and police crime prevention strategies. The results show that predictive policing based on data analysis and technology can improve police effectiveness in detecting perpetrator movement patterns, narcotics distribution channels, and radical propaganda. This is needed to optimize crime prevention strategies based on the crime triangle theory and differential association theory. Unfortunately, the implementation of predictive policing faces various challenges, ranging from limited access to accurate data, the risk of bias in analysis, and limited human resources to manage the technology. Therefore, the successful implementation of predictive policing requires support for regulatory improvements and increased police capacity to create a more effective and sustainable narcoterrorism prevention strategy.